Topics in Applied Econometrics Income Distribution and Demand Analysis - Planning Commission (Planning Commission, 1982)
Growth with social justice has been one of the basic objectives of the Indian Planning. The Sixth Five Year Plan has also emphasised the objective of progressive reduction in the incidence of poverty, unemployment and regional inequalities. Economic development requires not only a higher growth rate of per capital income but also a less unequal distribution of income and wealth. The eradication of poverty and reduction of social and economic inequalities are needed to achieve a better socio-economic order.
Government of India Planning Commission
Government of India Planning Commission